Impact of introduction of the 9-valent human papillomavirus vaccine on vaccination coverage of youth in North Carolina. Issue 10 (28th February 2018) - Trogdon, Justin G.; Shafer, Paul; Lindsay, Brianna; Coyne-Beasley, Tamera
Highlights: We evaluated the impact of a new 9vHPV vaccine on HPV vaccination rates. The new vaccine replaced the older version in the first year after release. The new vaccine was not associated with an overall change in HPV vaccination. Abstract: Objectives: The objective of this study was to evaluate the impact of introduction of 9vHPV vaccine on HPV vaccination uptake (doses per capita) and initiation (≥1 doses), completion (≥3 doses) and compliance (≥3 doses within 12 months) by adolescents. Methods: We used a retrospective cohort analysis using North Carolina Immunization Registry (NCIR) data from January 2008 through October 2016. The sample included Vaccines for Children eligible adolescents aged 9 to 17 years in 2016, for whom the NCIR contains complete vaccination history. We applied an interrupted time series design to measure associations between ZIP Code Tabulation Area (ZCTA)-level HPV vaccination outcomes over time with the introduction of 9vHPV in North Carolina (NC) in July 2015. Results: Each outcome displayed a linear upward trend over time with large seasonal spikes near August of each year, corresponding to the time when adolescents often receive other vaccines required for school entry. After accounting for these underlying trends, introduction of 9vHPV was not associated with a change in publicly funded HPV vaccination rates in NC. Conclusions: Our results indicate that 9vHPV substituted for 4vHPV in the first year after release in NC, but the release of 9vHPV was not associated with an overall change in HPV vaccination.